Consultation in primary care - Abdul Hadi, Azwanis; Abdullah, Fa’iza (IIUM Press, International Islamic University Malaysia, 2022)
This chapter includes definition, consultation structure and models; and barriers to good consultation. It is to ensure students know with a good understanding regarding consultation structure and barriers to a good consultation will ensure effective consultation skills in primary care. This chapter elaborates on the concept and general structure of consultation and its application in the medical setting. This will be followed by going through a few examples of consultation models to consolidate their understanding. It is recommended to read this chapter together with the chapter on “Communication skills in Primary care’ for prior knowledge. The estimated total number of words is 2495 and 13 printed pages including two tables and one picture.